Răspuns: a = 3
Explicație pas cu pas:
{10 - 2 × [ 1 + 3 : ( 2 a - 5 ) × 2 - 2 ] } × 5 + 10 = 10
{10 - 2 × [ 1 + 3 : ( 2 a - 5 ) × 2 - 2 ] } × 5 = 10 - 10
10 - 2 × [ 1 + 3 : ( 2 a - 5 ) × 2 - 2 ] = 0 : 5
10 - 2 × [ 1 + 3 : ( 2 a - 5 ) × 2 - 2 ] = 0
2 × [ 1 + 3 : ( 2 a - 5 ) × 2 - 2 ] = 10 - 0
1 + 3 : ( 2 a - 5 ) × 2 - 2 = 10 : 2
1 + 3 : ( 2 a - 5 ) × 2 - 2 = 5
1 + 3 : ( 2 a - 5 ) × 2 = 5 + 2
3 : ( 2 a - 5 ) × 2 = 7 - 1
3 : ( 2 a - 5 ) = 6 : 2
3 : ( 2 a - 5 ) = 3
2 a - 5 = 3 : 3
2 a - 5 = 1
2 a = 1 + 5
2 a = 6
a = 6 : 2
a = 3 → numarul, aflat prin metoda mersului invers